Joint optimization of spectrum sensing and accessing in multiuser multiple‐input single‐output cognitive networks. Issue 1 (4th August 2014) - Chen, Xiaoming; Yuen, Chau
Abstract: In this paper, a joint spectrum sensing and accessing optimization framework for a multiuser cognitive network is proposed to significantly improve spectrum efficiency. For such a cognitive network, there are two important and limited resources that should be distributed in a comprehensive manner, namely feedback bits and time duration. First, regarding the feedback bits, there are two components: sensing component (used to convey various users' sensing results) and accessing component (used to feedback channel state information). A large sensing component can support more users to perform cooperative sensing, which results in high sensing precision. However, a large accessing component is preferred as well, as it has a direct impact on the performance in the multiuser cognitive network when multi‐antenna technique, such as zero‐forcing beamforming, is utilized. Second, the tradeoff of sensing and accessing duration in a transmission interval needs to be determined, so that the sum transmission rate is optimized while satisfying the interference constraint. In addition, the aforementioned two resources are interrelated and inversive under some conditions. Specifically, sensing time can be saved by utilizing more sensing feedback bits for a given performance objective. Hence, the resources should be allocation in a jointly manner. Based on the joint optimization framework and the intrinsic relationship between the two resources, we propose two joint resource allocation schemes by maximizing the average sum transmission rate in a multiuser multi‐antenna cognitive network. Simulation results show that, by adopting the joint resource allocation schemes, obvious performance gain can be obtained over the traditional fixed strategies.Copyright © 2014 John Wiley & Sons, Ltd. Abstract : This paper proposes a joint spectrum sensing and accessing optimization framework for a multiuser cognitive network to significantly improve spectrum efficiency. On the basis of the joint optimization framework, feedback bits and time duration are jointly allocated, and thus obvious performance gain can be obtained over the traditional fixed strategies.